Pembentukan Karakter Kepemimpinan Santri Wati Melalui Ekstrakurikuler Oriskorh Di Pondok Pesantren Ar-Raudhatul Hasanah Medan - Darin Nazhifah; Ihsan Satrya Azhar (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
To face technological developments and increasingly complex social dynamics. This study aims to identify the leadership values of female students, supporting factors, and obstacles to the implementation of activities from ORISKORH extracurricular activities at Pesantren Ar-Raudhatul Hasanah in Medan. This research uses descriptive qualitative methods. Criteria for selecting informants include informants directly involved in the implementation of activities. In this study, the selected informants numbered 4 people, consisting of 1 mentor, 1 activity chairperson, 1 administrator, and 1 female student participating in ORISKORH activities.  Research results show that ORISKORH has several main activities: Independent assignments, public speaking exercises, debates, broadcasting (information dissemination), and evaluation & feedback. These activities form values of responsibility, discipline, self-confidence, communication, cooperation, independence, and decision-making through speech training, debates, broadcasting, tasks, and mentor evaluations. Supporting factors include facilities, environment, and management, while the main obstacle is time constraints. The implications of this research reinforce the concept of social learning and moral action as well as provide recommendations for managing pesantren extracurricular activities in developing female students' leadership with integrity and adaptability.